Prognostic and predictive value of AJCC-8 staging in the phase III EORTC1325/KEYNOTE-054 trial of pembrolizumab vs placebo in resected high-risk stage III melanoma. (July 2019) - Eggermont, Alexander M.M.; Blank, Christian U.; Mandala, Mario; Long, Georgina V.; Atkinson, Victoria G.; Dalle, Stéphane; Haydon, Andrew; Lichinitser, Mikhail; Khattak, Adnan; Carlino, Matteo S.; Sandhu, Shahneen; Larkin, James; et al.
Abstract: Background: The American Joint Committee on Cancer-8 (AJCC) classification of melanoma was implemented in January 2018. It was based on data gathered when checkpoint inhibitors were not used as adjuvant therapy in stage III melanoma. The European Organization for Research and Treatment of Cancer (EORTC) 1325/KEYNOTE-054 double-blind phase III trial evaluated pembrolizumab vs placebo in AJCC-7 stage IIIA (excluding lymph node metastasis ≤1 mm), IIIB or IIIC (without in-transit metastasis) patients after complete lymphadenectomy. Patients, methods and results: Patients (n = 1019) were randomised 1:1 to pembrolizumab 200 mg or placebo every 3 weeks (total of 18 doses, ∼1 year). At 1.25-year median follow-up, pembrolizumab prolonged relapse-free survival (RFS) in the total population (1-year RFS rate: 75.4% vs 61.0%; hazard ratio [HR] 0.57; logrank P < 0.0001) and consistently in the AJCC-7 subgroups. Prognostic and predictive values of AJCC-8 for RFS were evaluated in this study. Patient distribution according to the AJCC-8 stage subgroups was 8% (IIIA), 34.7% (IIIB), 49.7% (IIIC), 3.7% (IIID) and 3.8% (unknown). AJCC-8 classification was strongly associated with RFS (HRs for stage IIIB, IIIC and IIID vs IIIA were 4.0, 5.7 and 12.2, respectively) but showed no predictive importance for the treatment comparison regarding RFS (test for interaction: P = 0.68). The 1-year RFS rate for pembrolizumab vs placebo and the HRs (99% confidence interval) within each AJCC-8 subgroup were as follows: stage IIIA (92.7% vs 92.5%; 0.76 [0.11–5.43]), IIIB (79.0% vs 65.5%; 0.59 [0.35–0.99]), IIIC (73.6% vs 53.9%; 0.48 [0.33–0.70]) and IIID (50.0% vs 33.3%; 0.69 [0.24–2.00]). Conclusions: AJCC-8 staging had a strong prognostic importance for RFS but no predictive importance: the RFS benefit of pembrolizumab was observed across AJCC-8 subgroups in resected high-risk stage III melanoma patients. Highlights: AJCC-8 staging had a strong prognostic importance, overall and each treatment group. The estimated treatment hazard ratio stratified by the AJCC-8 staging was 0.54. No predictive importance of AJCC-8 staging could be observed. Treatment differences were consistent across AJCC-8 subgroups. Longer follow-up is required to assess the treatment difference in AJCC-8 stage IIIA.